Impact of radical treatments on survival in locally advanced T4a and T4b buccal mucosa cancers: Selected surgically treated T4b cancers have similar control rates as T4a. (July 2018) - Mair, Manish D.; Sawarkar, Noopur; Nikam, Santosh; Sarin, Rajiv; Nair, Deepa; Gupta, Tejpal; Chaturvedi, Pankaj; D'cruz, Anil; Nair, Sudhir
Highlights: Largest prospective series of treatment naïve 210 T4 buccal mucosa cancer patients. T4a disease was seen in 64.3% patients and T4b in 35.7% patients. Significant difference in 3-year disease-free survival between T4a & T4b cases. T4b patients with adequate cut margins had similar local control. NCCN favors non-surgical treatments; we propose surgery for infra-notch T4b cancers. Abstract: Introduction: In the absence of any robust data supporting the TNM classification of T4 buccal mucosa cancers, we did this prospective study to compare the oncologic outcomes of T4a and T4b buccal mucosa cancer patients. Patients and methods: This is a prospective study of 210 treatment naïve T4 buccal mucosa cancer patients. All patients underwent upfront radical surgery followed by adjuvant radiotherapy (RT)/chemoradiotherapy (CCRT). This is the largest prospective series in the literature on T4 buccal cancers. Results: T4a disease was seen in 135(64.3%) patients and T4b in 75(35.7%) patients. On comparison between all T4a and T4b cases, a significant difference was observed with regard to 3-year local control (49.6% vs. 41.1%: p-0.025) and disease-free survival (DFS) (65.3% vs. 42%: p-0.035) with a slightly higher incidence of distant metastasis in T4b patients (17.3% vs. 9.6%). Inadequate cut margin (<5 mm) was seen only in 7.4% patients with T4a disease and 12% patients with T4b disease. When patients with adequate cut margins were considered for analysis, local recurrence rate was similar for T4a (26/135; 19.3%) and T4b (15/66; 22.7%) disease suggesting the importance of radical surgery in infra-notch T4b buccal cancers. While the 3-year survival for T4a patients who received adjuvant RT alone was 72.2%, it was only 42.1% for similar T4b patients suggesting a need to intensify adjuvant treatment for these patients. Conclusion: Surgery should be considered as the primary modality of treatment for T4b patients, where clear margins are achievable. The benefit of treatment intensification with adjuvant CCRT should be explored in T4b buccal cancers.